Safety assessment of neurokinin-1 receptor antagonist: real-world adverse event analysis from the FAERS database - Yang, Chuanli; Xu, Pengyang; Wu, Teng; Fan, Yunhe; Li, Qingqing; Zhang, Jijun; Shen, Xiaobing; Dong, Xiushan (Frontiers in Pharmacology, 2024)
Background: Aprepitant, fosaprepitant, and netupitant are three common neurokinin 1 receptor antagonists (NK-1RAs) used to prevent chemotherapy-induced nausea and vomiting following highly or moderately emetogenic chemotherapy. Understanding their different adverse events (AEs) profiles may help clinicians make appropriate treatment decisions.Methods: All data collected from the FDA Adverse Event Reporting System (FAERS) database from the first quarter of 2004 to the fourth quarter of 2023 underwent disproportionality analysis to detect, evaluate, and compare AE signals of the three NK-1RAs.Results: A total of 3,904, 1,123, and 243 AE reports related to aprepitant, fosaprepitant, and netupitant, respectively, were extracted from the FAERS database. Of these, more than 50% of respondents were female, and the largest number were aged 45-65 years. General disorders and administration site conditions, and gastrointestinal disorders were the most frequently signals in system organ class of the three NK-1RAs drugs. In addition, aprepitant was strongly associated with joint deposit (ROR = 26.27), and fosaprepitant was closely related to seizure like phenomena (ROR = 26.90), two preferred term (PTs) were not mentioned in the manual. Statistically, netupitant was likely to induce death (N = 63, ROR = 8.78, 95% CI: 6.75-11.42). Additionally, neutropenic colitis, colitis, and stomatitis were unique to Netupitant. Furthermore, the AE profiles of the three NK-1RA drugs were different by gender.The AE profiles for aprepitant, fosaprepitant, and netupitant were different.Additionally to paying attention to common AEs, clinicians need to pay attention to new emerging AEs, such as joint deposit, seizure like phenomena, neutropenic colitis, colitis, and stomatitis, regarding the three NK-1RAs drugs. Furthermore, the AE compositions of the three NK-1RA drugs were different in different genders, and clinicians should take these factors into account when selecting NK-1RAs for CINV treatment.